2009
DOI: 10.1038/nri2470
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 and glucocorticoids as effectors of the resolution of inflammation

Abstract: Glucocorticoids are widely used for the management of inflammatory diseases. Their clinical application stems from our understanding of the inhibitory effect of the corticosteroid hormone cortisol on several components of the immune system. Endogenous and exogenous glucocorticoids mediate their multiple anti-inflammatory effects through many effector molecules. In this Opinion article, we focus on the role of one such effector molecule, annexin A1, and summarize the recent studies that provide insight into its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
801
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 796 publications
(836 citation statements)
references
References 83 publications
21
801
0
14
Order By: Relevance
“…AnxA1 is another GC-induced protein that has been shown to be anti-inflammatory and proresolving in various animal models of inflammation and in physiological conditions (4). Indeed, AnxA1 limits initial steps of inflammation, specifically the recruitment of leukocytes and generation of proinflammatory mediators.…”
Section: R Esolution Of Inflammation Is An Active and Continuousmentioning
confidence: 99%
See 1 more Smart Citation
“…AnxA1 is another GC-induced protein that has been shown to be anti-inflammatory and proresolving in various animal models of inflammation and in physiological conditions (4). Indeed, AnxA1 limits initial steps of inflammation, specifically the recruitment of leukocytes and generation of proinflammatory mediators.…”
Section: R Esolution Of Inflammation Is An Active and Continuousmentioning
confidence: 99%
“…Exploiting these physiological effects, GCs are among the most important drugs that have been developed for the treatment of inflammatory diseases. However, metabolic side effects of GCs limit their therapeutic application (4)(5)(6). The mechanisms of GCs are complex and depend on inhibition of transcription factors, such as NF-kB and AP-1, as well as induction of anti-inflammatory regulatory proteins such as annexin A1 (AnxA1), GC-induced leucine zipper (GILZ), and MAPK phosphatase (MKP)-1 (3).…”
Section: R Esolution Of Inflammation Is An Active and Continuousmentioning
confidence: 99%
“…Proteomic analysis, for example, revealed that purified influenza A virus (IAV) particles contain annexins A1, A2, A4, A5, and A11 (Shaw et al, 2008). Annexin A1 (AnxA1) is one of the most famous family members and there is a wealth of information on its protective anti-inflammatory and proresolving effects (Perretti and D'Acquisto, 2009 (Kattenhorn et al, 2004;Dry et al, 2008;Loret et al, 2008;Vidick et al, 2013), human immunodeficiency virus type 1 (HIV-1) (Chertova et al, 2006), vesicular stomatitis virus (VSV) (Moerdyk-Schauwecker et al, 2009, Rift Valley fever virus (Nuss et al, 2014) and IAV (Shaw et al, 2008), and recent evidence points to a function of the AnxA1 receptor FPR2 in IAV replication (Tcherniuk et al, 2016). AnxA2 is a component of herpesviruses (Wright et al, 1994(Wright et al, , 1995Varnum et al, 2004;Zhu et al, 2005;Dry et al, 2008;Loret et al, 2008;Gershom et al, 2012;Vidick et al, 2013), IAV (LeBouder et al, 2008;Shaw et al, 2008;Liu et al, 2012), HIV-1 (Chertova et al, 2006), human papilloma virus (HPV) type 16 (Woodham et al, 2012), hepatitis C virus (HCV) type 1 (Backes et al, 2010), VSV (Moerdyk-Schauwecker et al, 2009, vaccinia virus (Chung et al, 2006), Rift Valley fever virus (Nuss et al, 2014) and Newcastle disease virus (Ren et al, 2012).…”
Section: Annexins As Host Cell Derived Virulence Factorsmentioning
confidence: 99%
“…ANXA1 has pleiotropic and pluripotent effects in several biological processes, including infl ammation and tumorigenesis (19) (20) (23) . However, the role of ANXA1 in adaptive immunity is poorly defi ned.…”
Section: Anxa1 Expressionmentioning
confidence: 99%
“…Annexin A1 (ANXA1), also known as lipocortin-1, is a 37-kDa calcium-and phospholipid-binding protein involved in several biological processes, including suppression of infl ammation (16) (17) (18) . Indeed, ANXA1 modulates leukocyte extravasation to the site of infl ammation and regulates cytokine release in acute, chronic, or systemic infl ammation (19) (20) .…”
mentioning
confidence: 99%